Cattle Waste Management Strategy for Environmental Health in Pucangarum Village, Baureno District, Bojonegoro Regency - Mohammad Sholikin; Jati Batoro; Wresty L. Anggayasti; Maharani Pertiwi (Postgraduate, University of Mataram, 2024)
Livestock farming is one of the economic supporting sectors in Pucangarum Village, Baureno District, Bojonegoro Regency, East Java. The number of cattle in this village has increased from year to year by 31.29%. To maintain the sustainability of this cattle business, new breakthroughs are needed to eliminate the negative impact on the environment caused by livestock waste. The aim of the research is to find a waste management strategy in Pucangarum Village that is able to maintain the carrying capacity and capacity of the environment. Quantitative methods were used in this research. The analysis used is SWOT and AHP analysis to find priority strategies for the above problems. The results of strategy analysis using SWOT and AHP analysis show that the most suitable strategy to use in Pucangarum Village is a combination of Strength and Opportunity (SO), namely by providing regular counseling and assistance to breeders, provide training on processing livestock waste (biogas, fertilizer, etc.), provide education regarding the potential for waste processing to generate money or save electricity (biogas) and the government provides assistance in creating communal biogas installations.